Impact of Natural Gas and Biogas on Engine Lube Oil Condition - Hayat, N.; Mughal, H. U.; Nabiand, H. Z.; Moeenuddin, G. (The Nucleus, 2017)
The performance of lube oil condition with both natural gas and biogas as fuel has been investigated for a Genset having 1 mega-watt capacity. The algorithm based oil change intervals between 30-1042 hours and 30-300 hours; following a normal distribution, were employed for natural gas and biogas respectively. Test samples after full load operation were collected for laboratory analysis. The results show that there is accelerated lube oil dilution with biogas and oil change interval is one third of natural gas. Significant sulfur deposits on inner cylinder surface with natural gas were observed. Total base number (T.B.N), kinematic viscosity, oxidation and iron debris in lube oil followed similar trends. However, nitration and copper debris showed different patterns for natural gas and biogas during condition monitoring of lube oil.